PEDAGOGICAL MONITORING OF PROFESSIONAL TRAINING FUTURE SPECIALISTS IN THE SOCIAL SPHERE IN THE PROCESS OF APPLICATION OF ELECTRONIC LEARNING - KARPENKO, Olena (Social work and education, 2024)
The article examines the content of pedagogical monitoring of e-learning of future social workers in higher education institutions.The modern level of e-learning in the institution of higher education has been revealed. Special forms and methods of working with students - future specialists in the social sphere are analyzed and substantiated. The list of necessary conditions for the formation of applicants for higher education with a system of theoretical knowledge, practical abilities and skills necessary for the effective realization of oneself as a professional social worker is provided; development and formation of theoretical knowledge that will contribute to the development of the student as a future specialist in the social sphere.The purpose of the article is to identify the problems of professional training and to study the special requirements for the development and implementation of electronic training courses in the process of professional training of social sector specialists capable of solving social problems. Considerable attention is paid to the problems of pedagogical interaction between the teacher and the student, based on the analysis, the strengths of e-learning are highlighted, and the expediency of its use is clarified.The main tasks are defined as follows: to identify and generalize the components of professional self-development as one of the complex forms of transformation of the inner world, which occurs in the process of self-movement of a person along his life path, on which a person knows himself, builds himself, understands the essence of his functioning; to investigate the peculiarities of vocational pre-university education as a focus for personal development on self-building, professional self-determination for the successful growth of professionals in the social sphere.Based on the results of the generalized analysis, it was concluded that the effectiveness and feasibility of e-learning takes into account not only the general principles of learning, but also the specifics of a specific field or subject. These technologies allow students to independently organize their educational process, develop independent work skills and improve their knowledge.The proposed e-learning technologies can be used in universities, faculties and departments where future specialists in social spheres are trained, as well as in advanced training courses with the aim of increasing readiness to interact with clients based on mastering a set of knowledge and skills aimed at transforming informational and reflective, professional-practical and professional-development technologies in the real conditions of the environment of the higher education institution.The conclusions confirmed the substantiation of the necessary pedagogical conditions for improving the quality of extracurricular activities in the environment of institutions of professional pre-higher education regarding future social workers in the conditions of globalization.